AVALIAÇÃO FUNCIONAL DA PESSOA IDOSA EM SITUAÇÃO DE FRAGILIDADE INSERIDA EM PROGRAMAS DE FISIOTERAPIA DO SETOR PÚBLICO E PRIVADO - Grangeiro, Adriano Filipe Barreto (2015)
The growth of the elderly population is a worldwide phenomenon and a major challenge to public health, especially in developing countries like Brazil. Significant changes in morbidity and mortality indicators in this country are noticeable and may affect the functionality resulting in loss of autonomy and independence. Thus, evaluation studies that provide know the specifics of the elderly related to their ability to perform daily living of Basic Activities are essential for structuring programs for prevention and therapeutic decision-making. Objective: To study the functional clinical profile of the elderly in fragile situations met in the home environment of the public sector and private sector in Sao Luis, MA. Methods: analytical character of cross sectional study. The sample consisted of 241 elderly participating in home physical therapy programs in the public and private sector. The data collection instruments used were: Health Handbook for the Elderly and the Barthel Index. Data were analyzed using SPSS software. Results: Both groups were mostly women, aged 80-89 years, of brown color, retirees, living with their families and in need of daily care. A significant association with the type of service the public or private sector in the variables marital status (p = 0.000), educational level (p = 0.000) and income (p = 0.000). Main morbidities by the elders of both groups were the Circulatory System Diseases averaging 85.7% of respondents. There was a higher prevalence of elderly in the private sector (57%) with total dependence to perform the Basic Activities of Daily Living and only 36.9% in the elderly public sector. In the elderly the public sector showed a significant association with the occurrence of falls (p = 0.0391), medication use (p = 0.0192) and previous hospitalization (p = 0.0008) and in the private sector elderly variables with statistically significant difference were: occurrence of falls (p = 0.0391) and medication use (p = 0.0192) when associated with the degree of functional dependence. Conclusion: It was noticed a more severe degree of dependence among the elderly in the private sector when compared to those of the public sector. There was thus demonstrates the importance of extending and improving the quality of life of older people through the expansion of home-based programs with interdisciplinary care for this age group.